On-Site Emission Inventory for Port Areas Along Soai Rap Navigation Channel, Vietnam - Pham, Thanh Tuan; Ho, Quoc Bang; Ho, Minh Dung; Ho, Quoc Bao; Tran, Thi Nguyet Minh (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2026)
The Soai Rap navigation channel in southern Vietnam, spanning 66.6 km and hosting 12 ports and 15 mooring buoys, is undergoing expansion to support regional socioeconomic development. This study aimed to quantify the on-site CO2 emissions from maritime and port activities along the channel. A combination of bottom-up and top-down emission inventory approaches was applied,focusing on ships (anchoring and maneuvering) and cargo handling equipment, with spatial analysis conducted using QGIS. The results show that ships are the dominant emission source, contributing 1.116 million tons of CO2, compared with 4.344 thousand tons from cargo handling equipment, out of a total of 1.12 million tons. Bo Bang anchorage accounted for most of the emissions (89.82%),followed by Tan Cang Hiep Phuoc Port (5.85%). Scenario analysis indicates that introducing shore power could reduce emissions by 35.09–99.79%, whereas the electrification of cargo handling equipment could reduce emissions by 0.53–64.53%. Combining both measures yields reductions of 93.03–99.79%. These findings provide evidence for green port development strategies and local airquality improvements. This study highlights the urgent need to expand berth capacity and implement electrification measures and management policies to effectively mitigate port-related emissions.